Design a challenge-based learning model for higher education, an application in a beverage company - Da Silva-Ovando, Agatha Clarice; Olivares Quintana, Oscar Saúl; Salinas-Navarro, David Ernesto; Chong, Mario (IEEE, 2022)
As the students’ profile and the industry’s expectations change over time, universities must adopt learning methodologies to deliver more suitable graduates to the labor market. The Universidad Privada Boliviana (UPB) has been developing experiential learning practices by implementing challenge-based learning (CBL) to enrich undergraduates’ curricula. One example reflected in the CBL experiences developed by Taquiña Brewery, one of the five breweries of the Cervecería Boliviana Nacional (CBN), and the Industrial and Systems Engineering Department of the UPB between 2018 and 2019. As a result, the students widely accepted the methodology, and academics from all disciplines were trained to replicate CBL experiences in their classrooms. While CBN found the opportunity to hire new talent, receive a fresh perspective on recurrent operational issues, and find new ideas based on theoretical concepts. This work contributes to the exemplification of innovative approaches to enhance the teaching and learning of Supply Chain Management and Logistics. ©The authors, IEEE.
Keywords: Supply chain management; Conferences; Companies; Modeling; Engineering education; Logistics